STRATEGIC VIGILANCE AND ITS ROLE IN CREATING VALUE FOR THE CUSTOMER: AN EXPLORATORY STUDY OF A SAMPLE OF WORKERS IN THE NORTHERN GENERAL CEMENT COMPANY - Iman Najmaldin Abdullah (Scholars Digest Publishing, 2023)
The study aimed to define the role of strategic vigilance in creating customer value. The study is on the correlation and influence relationships between strategic vigilance and customer value, The Northern General Cement Company was selected as a community for the study and its employees a sample of (50), and the descriptive analytical approach was used to achieve the desired goals, and the questionnaire was adopted as a tool in data collection, and the data were analyzed using the package (SPSS V-26) The study came out with a set of conclusions, the most important of which are: Strategic vigilance plays a major role in creating the value for the customer that he desires, and the surveyed organization has a good level of strategic vigilance by monitoring the external environment and standing on the most prominent changes to help it invest in the opportunities.
Keywords: Strategic, vigilance, Strategic vigilance, creating, Customer value.